Synthesis and biological activities of pyridine N-oxide bearing 5-aminoisoxazoles as potential acetylcholinesterase and monoamine oxidase inhibitors for Alzheimerʼs disease - Saleh, Lange Yakubu; Özdemir, Soner; Sağlık, Begüm Nurpelin; Döndaş, H. Ali; Altug, Cevher (Elsevier B.V., 2025)
A series of ten novel pyridine N-oxide-bearing 5-aminoisoxazoles was efficiently synthesized in moderate yields by reacting 2-(cyanomethyl)pyridine 1-oxide with α-chlorooximes, employing sodium ethoxide as a base. The synthesized compounds were verified with a variety of spectra. Subsequently, the inhibitory potency of compounds 4c, 4e, 4f, 4h, and 4i against AChE and BChE, primary targets in Alzheimer's disease, was assessed. In silico docking analyses were conducted to evaluate the interaction of compounds 4c, 4e, 4f, 4h, and 4i with AChE and MAO-B. Among the tested compounds, 4e and 4h demonstrated remarkable AChE inhibition, exhibiting IC50 values of (0.050 µM and 0.039 µM, respectively), comparable to the inhibition achieved by donepezil (IC50 = 0.020 µM). Additionally, compounds 4c, 4e, 4f, 4h, and 4i displayed potent MAO-A inhibition, with IC50 values of (0.203, 0.067, 0.083, 0.044, and 0.159 µM, respectively), surpassing the efficacy of moclobemide (IC50 = 6.061 µM). Compounds 4e, 4f, and 4h also inhibited MAO-B, with IC50 values of (0.076, 0.058, and 0.049 µM, respectively), close to the inhibitory effects of Selegiline (IC50 = 0.037 µM). Compound 4h emerged as a multi-target inhibitor, effectively inhibiting AChE, MAO-A, and MAO-B. These findings underscore the therapeutic potential of these novel compounds in the treatment of Alzheimer's disease, warranting further investigation into their clinical application.